PENGEMBANGAN TUNGKU PELEBURAN ALUMINIUM UNTUK MENGEMBANGKAN KOMPETENSI PENGECORAN DI SMK PROGRAM STUDI KEAHLIAN TEKNIK MESIN - uny, lppm (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The program is aimed at developing casting competence at SMK Muhammadiyah Prambanan Yogyakarta by developing gas fueled aluminium crucible furnace. Research and development method was used to develop aluminium crucible furnace. Training on crucible furnace operation and aluminium casting for SMK Muhammadiyah teachers was done using demonstration and lecture method. The program result is (í˜600x500)mm crucible furnace with capacity of 15 kg melted aluminium. The furnace need 2,7 kg of LPG and 55 minutes to melt 8,6 kg aluminium. SMK Muhammadiyah Prambanan teachers are able to operate the furnace, to make a sand mold and to do a daily and special maintenance